MR Imaging of Salivary Duct Carcinoma - Motoori, Ken; Iida, Yumiko; Nagai, Yuichirou; Yamamoto, Seiji; Ueda, Takuya; Funatsu, Hiroyuki; Ito, Hisao; Yoshitaka, Okamoto (American Journal of Neuroradiology, 2005)
BACKGROUND AND PURPOSE: Salivary duct carcinoma (SDC) is regarded as a high-grade malignancy in the current classification of salivary gland neoplasms. The aim of our study was to describe the MR imaging features of SDC.METHODS: Nine patients with SDC underwent MR imaging study. The apparent diffusion coefficient (ADC) values of SDCs were measured from diffusion-weighted images. Time–signal intensity curves (TICs) of the tumors on dynamic MR images were plotted, and washout ratios were also calculated. TICs were divided into four types: type A, curve peaks <120 seconds after administration of contrast material with high washout ratio (≥30%); type B, curve peaks <120 seconds with low washout ratio (<30%); type C, curve peaks >120 seconds; type D, nonenhanced. We correlated the MR findings of SDC with the pathologic findings.RESULTS: All tumors had ill-defined margins and showed low to moderately high signal intensity for contralateral parotid gland on T2-weighted images. The average of the ADC values of the SDCs was 1.16 ± 0.14 [SD] × 10−3mm2/s. Seven of nine (78%) tumors had type B enhancement. On the other hand, six of nine (67%) tumors with rich fibrotic tissue also had type C enhancement.CONCLUSION: The findings of ill-defined margin, early enhancement with low washout ratio (type B), and low ADC value (1.22 × 10−3mm2/s) were useful for suggesting malignant salivary gland tumors. Although it was reported that type C enhancement was specific for pleomorphic adenoma, SDC frequently has type C-enhanced focus.